Financial Governance Socialization for Public Organizations at the Community Empowerment Institution (LPM) of Rempoa Subdistrict - Yusuf, Y.; Fitri, Euis Nessia; Febriyanto, Muhammad Ikhsan (Golden Ratio of Community Services and Dedication, 2025)
This community service program aims to improve financial governance in public organizations through a case study at the Community Empowerment Institution (LPM) of Rempoa Subdistrict. The LPM plays a key role in grassroots development but faces challenges in budget planning, bookkeeping, financial reporting, and internal control. The program employed participatory methods, including socialization, workshops, technical assistance, and focus group discussions. Results show a significant increase in participants’ understanding of public financial principles, with 75% able to draft simple budgets and 50% capable of accurate transaction recording. The program also led to the development of a basic internal control mechanism adopted by 80% of participants. These outcomes indicate that targeted interventions can strengthen transparency and accountability in local institutions. This initiative highlights the importance of capacity building and practical tools in empowering community organizations. Ongoing support and digital integration are recommended to sustain these improvements.